The Implementation and Reflection of Genre-Based Writing in Online Learning to Enhance Writing Achievement - An Nafik, Aulia (English Education Journal, 2023)
This study aimed to investigate the implementation and reflection of a genre-based writing approach in synchronous online learning to enhance the writing achievement of EFL students. It involved the lecturer and students in the third semester of the three-year diploma in English, which employed a mixed-method research design. The inter-rater evaluation was used in scoring the students’ pre-test and post-test. All the paired t-test results revealed a significant difference in writing achievement before and after the intervention, with the average mean value of the pre-test (M= 70.5) and post-test (79.75). On the other hand, the qualitative data analysis from the students’ diaries and reflective journals revealed that connection-related issues were the major hindrance to having GBW in an online environment. However, the students claimed that online learning offered flexibility, which did not decrease the effectiveness and essence of the lesson itself. In the reflection, the lecturer justified the flexibility of online learning, yet he tended to choose the offline mode for teaching writing in consideration of academic integrity. In summary, implementing genre-based writing in synchronous online learning for university students showed much potential for enhancing students’ writing achievement. Through the benefits of remote learning, the adaptation to the unique needs of learners, and the integrity of academics, teachers and educators can effectively conduct educational or academic activities. The implications of this study go beyond the boundaries. It influences the current discourse about the role of technology in education and its future.